Vaccines targeting preS1 domain overcome immune tolerance in hepatitis B virus carrier mice. Issue 4 (26th August 2017) - Bian, Yingjie; Zhang, Zheng; Sun, Zhichen; Zhao, Juanjuan; Zhu, Danming; Wang, Yang; Fu, Sherry; Guo, Jingya; Liu, Longchao; Su, Lishan; Wang, Fu‐Sheng; Fu, Yang‐Xin; et al.
Abstract : Strong tolerance to hepatitis B virus (HBV) surface antigens limits the therapeutic effect of the conventional hepatitis B surface antigen (HBsAg) vaccination in both preclinical animal models and patients with chronic hepatitis B (CHB) infection. In contrast, we observed that clinical CHB patients presented less immune tolerance to the preS1 domain of HBV large surface antigen. To study whether targeting the weak tolerance of the preS1 region could improve therapy gain, we explored vaccination with the long peptide of preS1 domain for HBV virions clearance. Our study showed that this preS1‐polypeptide rather than HBsAg vaccination induced robust immune responses in HBV carrier mice. The anti‐preS1 rapidly cleared HBV virions in vivo and blocked HBV infection to hepatocytes in vitro . Intriguingly, vaccination of preS1‐polypeptide even reduced the tolerized status of HBsAg, opening a therapeutic window for the host to respond to the HBsAg vaccine. A sequential administration of antigenically distinct preS1‐polypeptide and HBsAg vaccines in HBV carrier mice could finally induce HBsAg/hepatitis B surface antibody serological conversion and clear chronic HBV infection in carrier mice. Conclusion : These results suggest that preS1 can function as a therapeutic vaccine for the control of CHB. (Hepatology 2017;66:1067‐1082)